Dissolution of Different Reservoir Rocks by Organic Acids in Laboratory Simulations: Implications for the Effect of Alteration on Deep Reservoirs - Jian Chen; Jie Xu; Susu Wang; Zhenyu Sun; Zhong Li; Wanglu Jia; Ping’an Peng (Geofluids)
Organic acids are important agents in the alteration of deep reservoirs. It is difficult, however, to assess the impact of organic acid alteration on deep reservoirs because different dissolution processes may occur during diagenesis. This study simulated the dissolution of three different types of reservoir rocks by acetic acid in a closed system and compared the mineral and elemental composition, surface morphology, pore structure, and water chemistry variations of the initial and altered samples. The study demonstrated that both micrite and sucrosic dolostone are strongly dissolved, losing about 20%–30% of their initial rock sample weights. Observation under SEM showed that the limestone dissolved homogenously, whereas the dolostone showed honeycomb-like dissolution. Both carbonate samples showed the development of large voids, including holes and cavities of micrometer scale, but nanopores of various sizes were blocked. In contrast, lithic arkose was heterogeneously altered, losing a weight proportion of about 13% by dissolution of calcite cement. These micrometer-scale microfissures were developed, but those nanometer-scale pores just varied in a narrow range of sizes. The volume increase in all three reservoir types is mainly attributed to the dissolution of carbonate minerals. In deep reservoirs, in situ generated organic acids can enlarge existing cavities in carbonates and develop microfissures in sandstones. The microfissure porosity in sandstone is limited but can increase through other geological processes such as overpressure. More importantly, these acids can maintain the acidity of pore waters, inhibit the precipitation of dissolved minerals, and help to preserve reservoir porosity. Although temperature plays an insignificant role in laboratory simulations, it influences both the generation and destruction processes of organic acids in deep reservoirs on geologic time scales and, thus, warrants further attention. The results provide a basis for recognizing the typical patterns of organic acid dissolution on different reservoir rocks and further suggest the potential role of organic acids in the formation and preservation of secondary porosity in deeply buried reservoirs.